Perbandingan Kualitas Hidup Nelayan Berdasarkan Modernitas Individu - Eka Apriyanti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2020)
Quality of life is a part of development concept which usually used for finding out the Human Development Index (HDI) that was determined by enrollment rate, life expectation, Gross Domestic Product (GDP) of each country. The research was aimed at finding out the differences of fishermen’s Quality of Life (QoL) based on individual modernity. An expost facto was used by involving 155 fishermen as sample. There were two instruments for measuring fishermen QoL (18 items, rel .816) and individual modernity (17 items rel .845). Data was analyzed by t test. The results revealed that there was significant differences of fishermen’s QoL between those who have high individual modernity compared to those who have lower individual modernity. Therefore, it could be concluded that fishermen’s QoL might be affected by individual modernity. The implication of this research would be beneficials for improving QoL instrument by considering the role of individual modernity concepts.